1996
DOI: 10.1002/bbpc.19961000812
|View full text |Cite
|
Sign up to set email alerts
|

Bond angle distribution in amorphous germania and silica

Abstract: The distribution of Ge-0-Ge and Si-0-Si bond angles a in amorphous germania and silica is re-determined on the basis of diffraction experiments. The bond angle a joining adjacent tetrahedra is the central parameter of any continuous random network description (CRN) of these glasses. New high energy photon diffraction experiments on amorphous germania (at photon energies of 97 and 149 keV) are presented, covering the momentum transfer 0.6-33.5 A -'. In photon diffraction experiments on GeO, the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
95
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 42 publications
28
95
2
Order By: Relevance
“…[17], but in agreement a more recent calculation that used a larger range of X-ray energies, and hence k as well [18]. Not including d-state symmetries with Gaussian radial components yield the ionic bonding solution with bond angle of 180…”
Section: Bonding Constraints For Sro and Mrosupporting
confidence: 78%
See 1 more Smart Citation
“…[17], but in agreement a more recent calculation that used a larger range of X-ray energies, and hence k as well [18]. Not including d-state symmetries with Gaussian radial components yield the ionic bonding solution with bond angle of 180…”
Section: Bonding Constraints For Sro and Mrosupporting
confidence: 78%
“…[20,21]. The staggered configuration in these studies is the geometric arrangement that is required by the symmetry constrains of the O 2pπ-Si 3dπ overlap that provides the charge transfer that stabilizes the Si-O-Si bond angle at a value consistent with the latest X-ray diffraction studies [18].…”
Section: Bonding Constraints For Sro and Mromentioning
confidence: 88%
“…The 9-atom clusters are terminated either by i) Si* pseudo-atoms that preserve Si and O core levels, and dipole moments, or ii) Hatoms with essentially equivalent results. The ab initio calculations give an average Si-O-Si bond angle of 149±1°, and a bond angle distribution of ~19°±2° in good agreement with recently published results [9,10]. This distribution is markedly different from the >30° bond angle spread of Mozzi and Warren [11].…”
Section: Ab Initio Calculationssupporting
confidence: 86%
“…A recent neutron and X-ray diffraction investigation [35] has shown that the o using high-energy X-ray diffraction [45]. This bond angle and its distribution are lower than in the case of vitreous silica.…”
Section: Neutron and X-ray Diffractionmentioning
confidence: 99%